Assessment of Task Demand and Usability of a Virtual Reality-Based Rehabilitation Protocol for Combat Related Traumatic Brain Injury From the Perspective of Veterans Affairs Healthcare Providers: A Pilot Study - Greenhalgh, Mark; Fitzpatrick, Christian; Rodabaugh, Timothy; Madrigal, Esmeralda; Timmerman, Molly; Chung, Joyce; Ahuja, Deeksha; Kennedy, Quinn; Harris, Odette A.; Adamson, Maheen M. (Frontiers in Virtual Reality, 2021)
The risk of traumatic brain injury (TBI) is significantly higher among Veterans compared to non-Veterans. Access to treatment for TBI and post concussive symptoms is sometimes difficult, because of barriers related to distance, finances, and public safety (i.e., COVID-19 infection). Virtual reality rehabilitation (VRR) offers an opportunity to incorporate a virtual space into a rehabilitation environment. To our knowledge, VRR has not been used to assist Veterans with TBI and related health problems with Instrumental Activities of Daily Living (iADLs). The purpose of this study is to investigate the usability of a novel VRR ADL and iADL training protocols, developed by the Gaming Research Integration for Learning Laboratory (GRILL®) at the Air Force Research Laboratory, for cognitive rehabilitation for Veterans with a TBI. We deployed a prototype protocol among healthcare providers (n = 20) to obtain feedback on usability, task demand, and recommended adjustments. Our preliminary analysis shows that providers found the VRR protocol involved low physical demand and would likely recommend it to their patients. Although they had some concerns with vertigo-like symptoms from using a digital technology, they believed the protocol would improve iADL functioning and was a good addition to pre-existing rehabilitation protocols. These outcomes provide justification for more impactful studies investigating the effectiveness of this protocol among Veterans with TBI.